Penerapan Pembelajaran Strategi Problem Based Learning (PBL) untuk Meningkatkan Keaktifan dan Hasil Belajar IPA/Biologi Bagi Siswa Kelas XI Ak 1 SMK Negeri 1 Banyudono Kabupaten Boyolali Semester Genap Tahun Ajaran 2011/2012 - SULASTRI, IKA SRI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2015)
In the classroom action research conducted has the goal that the implementation of the strategy learning model Problem Based Learning (PBL) can be used to enhance the activity and student learning outcomes. Implementation of classroom action research design was used classroom action research conducted by two cycles, each cycle consisting of 4 meetings, with research subjects Class XI AK 1 number of 40 students. Implementation of each cycle in the study consisted of four phases, namely: an action plan (Planning), action (acting), Observing and reflecting. Data collection activity of students in the application of strategic learning model Problem Based Learning (PBL), using observation techniques and data used as documentation of the final value. Research data analysis techniques are used as the final value of classical learning completeness of the final value. The calculation result obtained before the first cycle of learning outcomes with the lowest and highest 55, 90, 92.5% completeness study. After the first cycle of learning results obtained with the lowest value of 60 and 90 with the highest passing grade of 95%, after the second cycle study results obtained with the lowest value of 80 and the highest 100 with a 100% mastery learning. While active students in the first cycle of 69.2% and the second cycle by 76, 3%. With Action Research Classroom teachers can develop a variety of learning methods one with